Integration and International Dispute Resolution in Small States (The World of Small States,, 2018)
This book provides an insight into commercial relations between large economies and Small States, the benefits of regional integration, the role of Small States as financial centres as well as B2B and State to State dispute resolution involving Small States. Several contributions allow the reader to familiarise themselves with the general subject matter; others scrutinise the particular issues Small States face when confronted with an international dispute and discuss new and innovative solutions. These solutions range from inventive ideas to help economic growth to appropriate mechanisms of dispute resolution including inter-State dispute resolution and specific areas of arbitration such as tax arbitration. Researchers, policy advisors and practitioners will find a wealth of insights, information and practical ideas in this book.